The Effect of Telmisartan on Collagen Percentages by Picrosirius Staining in the Glomerular Renal Organ of 8% NaCl-Induced Rats - Khairil Pahmi; M Sidratullah; M Ricky Ramadhian (Journal Syifa Sciences and Clinical Research, 2020)
Excessive salt consumption is one of the hypertension and kidney disease factors, while telmisartan is one of antihypertensive drugs used in the therapy. Telmisartan not only blocks angiotensin receptor which leads to the decrease of blood pressure, but also activates peroxisome proliferator activated receptor gamma (PPAR-γ) and inhibits transforming growth expression factor of beta-1 (TGFβ-1). Whether telmisartan decreases the kidney collagen volume fraction of excessive NaCl-induced Wistar rats are studied in this experiment. Twenty five male Wistars 2.5-3 months of age and 100-150 g BW rats were used in this research. They were grouped into 5, each consists of 5 rats. Group I (G I) as first negative control did not receive NaCl and telmisartan. G II as second negative control received NaCl but not telmisartan. G III, IV and V received NaCl and telmisartan 3, 6 and 12 mg/kg BW. The treatments were given every day within 8 weeks. At the day of 56 all rats were sacrificed by mean of neck dislocation and operated to take the kidney. The collagen was stained by picrosirius red staining. Data were expressed as mean ± standard deviation. They were analyzed by parametric test (analysis of variance-ANOVA and paired samples t-test) or nonparametric test (Kruskal-Wallis). A value of p0.05 was considered statistically significant. The results showed that intraglomerular and extraglomerular collagen volume fraction were lower in telmisartan-treated Wistar rats group than negative control group (0.05p0.05). In conclusion, intraglomerular and extraglomerular collagen volume fraction were lower in 8% sodium chloride-induced and telmisartan-treated male Wistar rats than the items of negative control group.